Migration and Everyday Racism in East-central Europe: Editorial Note - Rodríguez Polo, Mario; Šotola, Jaroslav (Lidé města, 2018)
Recently, the discussion about migration in the East-Central European region has been framed in the terms of the increasing hysterical paranoia aimed at migrants under the blurring common label of “refugees”. Paradoxically, everyday reality is far from the announced “refugee invasion”, and the migration ratios are comparatively low. Sadly, xenophobic attitudes are maintained and performed not only by extremist political parties, but also by prominent figures in charge of key institutions, such as the Ministry of the Interior, police departments, and even reaching the prime ministers and presidents of the countries. Not only institutional figures actively contribute to the portrayal of migrants as a hazard to the region. Mainstream regional media also continuously provide bizarre and surreal xenophobic materials that spread through social networks, contributing to a social imaginary opposing migration. The impact and social consequences of such irresponsible behaviour is frequently muted. On one hand, only a few episodes of discrimination, racial aggressions, or criminal hate manifestations (constituting clear episodes of racism) get media coverage, while on the other hand, the everyday forms of racism remain muted and unconsidered.